2010
DOI: 10.1080/10691898.2010.11889472
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Attitude of Graduate Students in On-Campus vs. Online Statistics Courses

Abstract: This study compared levels of statistics anxiety and attitude toward statistics for graduate students in on-campus and online statistics courses. The Survey of Attitudes Toward Statistics and three subscales of the Statistics Anxiety Rating Scale were administered at the beginning and end of graduate level educational statistic courses. Significant effects were observed for two anxiety scales (Interpretation and Test and Class Anxiety) and two attitude scales (Affect and Difficulty). Observed decreases in anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 18 publications
7
65
1
6
Order By: Relevance
“…Investigating 177 students, they found that female students hold more negative attitudes towards statistics and rate their statistical competence lower than male students although they did not differ in their achievement. DeVaney (2010) showed that students felt less anxiety when enrolled in an online course whereas the anxiety in a traditional course persisted.…”
Section: Comparison Of Different Populations and Coursesmentioning
confidence: 99%
“…Investigating 177 students, they found that female students hold more negative attitudes towards statistics and rate their statistical competence lower than male students although they did not differ in their achievement. DeVaney (2010) showed that students felt less anxiety when enrolled in an online course whereas the anxiety in a traditional course persisted.…”
Section: Comparison Of Different Populations and Coursesmentioning
confidence: 99%
“…The assistant moderator was the current instructor for Focus Group 3. The number of participants in Focus Group 1 and Focus Group 3 was within the six to nine participants (Krueger, 2000), six to 10 participants (Langford, Schoenfeld, & Izzo, 2002;Morgan, 1997), and six to 12 participants (Bernard, 1995;Johnson & Christensen, 2010;Onwuegbuzie, Dickinson, Leech, & Zoran, 2009, 2010 recommended in the literature, with Focus Group 2 containing one less participant than the optimal size.…”
Section: Instruments and Proceduresmentioning
confidence: 99%
“…However, as noted by , focusing only on data generated by the groups can be very problemat-ic because group-based data alone (a) provide no information about the degree of consensus and dissent, (b) provide no information about other focus group members who might not have contributed to the category or theme, and (c) make it difficult to determine the degree to which the data that contributed to the theme reached saturation for the focus group (i.e., within-group data saturation; Onwuegbuzie, Dickinson, et al, 2009). As such, in the present study, we conducted what Onwuegbuzie, Dickinson, et al (2009, 2010 refer to as a micro-interlocutor analysis, which involves not only identifying and providing the most compelling statements made by focus group participants, but also providing information about how many members (or the proportion of members) contributed/did not contribute to each category or theme.…”
Section: Unit Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have noted that research courses also provoke anxiety in students (DeVaney, 2010;Green, Bretzin, Leininger, & Stauffer, 2001). Green et al (2001) compared research anxiety across various disciplines and found MSW students had higher anxiety than their counterparts regarding research methods and analysis.…”
mentioning
confidence: 99%